Antibacterial Activity of Some Non-steroidal Anti-inflammatory Drugs against Proteus mirabilis - Ghena Jameel Ibrahim; Bahaa Abdullah Laftaah AL-Rubaii (Ibn Al-Haitham Journal for Pure and Applied Sciences)
In some recent investigations, non-steroidal anti-inflammatory drugs (NSAIDs) and paracetamol demonstrated antibacterial action. This study aimed to evaluate the inhibitory effects of diclofenac, piroxicam, and paracetamol against multidrug-resistant Proteus mirabilis. The sensitivity of Proteus spp. was tested for nine antibiotics representing seven different families using an agar diffusion test. The isolates with multiple antibiotic resistances were selected to test the effect of NSAIDs and paracetamol on growth using a resazurin-based microplate broth dilution assay. The findings of the agar diffusion test revealed the highest level of antibiotic resistance for Proteus isolates was recorded against ceftazidime with a percentage of (91.53%) followed by amoxicillin-clavulanate and cefixime (81.36%) and (76.27%), respectively. The isolates were resistant to azithromycin at a rate of (69.49%). Furthermore, moderate resistance was observed among the isolates to levofloxacin (66.10%), gentamicin (55.93%), and aztreonam (47.46%). While the lowest resistance was reported (18.64%) against piperacillin-tazobactam and (8.47%) against imipenem, Imipenem had the greatest antibacterial activity (88%); also, NSAIDs showed distinct antibacterial activity against Proteus mirabilis in (2500, 5000 μg/ml) and above concentrations for piroxicam and diclofenac, respectively. Paracetamol failed to show antibacterial activity against Proteus mirabilis